TRANSITION TO ADULTHOOD FOR YOUNG PEOPLE WITH CARE EXPERIENCE IN CHINA - YIN, SHIAN (2023)
Internationally, there is increasing discussion about young people with experience of the care system. These individuals often experience negative outcomes after leaving care, such as housing insecurity, job instability, low-income level, early parenthood, and social exclusion. Related research conducted primarily in Western contexts and in family-based care reflects a situation of underrepresentation in which young people's voices from less-developed countries, such as China, and other care settings are less emphasised, and there is an incomplete understanding of the transition from childhood to adulthood for young people who have experienced care. To address these gaps, this study explores life experiences and perspectives of young people with care experience in China as they transition to adulthood. Participants included 34 care-experienced young adults and eight care staff members. A qualitative methodological approach was adopted using remote interviewing as the data collection method. Interview data were transcribed, translated, and then analysed through a six-phased thematic analysis. Based on life-course and resilience theories and perspectives such as social model of disability and stigma, research findings comprise four aspects. First, young people with experience of care in China proceed their transition to adulthood at different rates and through differing sequences of life events. Second, leaving care is an important life event during the transition to adulthood for this group of individuals as it results in significant changes in residential status, social roles, and the level of social support they receive. Third, the education, work and family formation pathways followed are significantly diverse. Similar to those in Western contexts, the transition to adulthood for those having been in care in China is associated with a series of disadvantages. Fourth, their transition to adulthood is fraught with various challenges and risks along the way. Despite some being able to transition more successfully when exposed to protective factors, the range and depth of support they received remains overall inadequate. As a result, this study proposes comprehensive responses that cover young people's three life stages to inform policymakers, service providers and local authorities of appropriate solutions to support this population in China.